Profesor Lucyna Turek-Kwiatkowska (1925–2017). Szczeciński archiwista i historyk - Magiera, Elżbieta (Biuletyn Historii Wychowania, 2017)
Professor Lucyna Turek-Kwiatkowska (1925–2017). Historian and Archivist of Szczecin Lucyna Turek-Kwiatkowska was a member of the community of Szczecin historians and archivists. She was the director of the State Archives in Szczecin and a professor at the University of Szczecin. She researched the history of Pomerania, history of West Pomeranian towns and cities, history of archives, education in Pomerania, development of historical awareness of Pomeranian society, material and spiritual culture in Pomerania in the 19th and in the first half of the 20th century. Her work had a pioneering character that supported the processes of social integration and adaptation in West Pomerania.